Analisis Perlakuan Akuntansi Persediaan Berdasarkan PSAP Nomor 05 Pada Badan Pendapatan Daerah Kota Bitung - Mandolang, Rayzinsky Clarents; Saerang , David Paul Elia; Pangerapan, Sonny (Universitas Sam Ratulangi, 2024)
Inventory is equipment or goods that are in a government agency to be used to support or will be provided as a service to the community. Inventory is very important for companies, such as trading companies, manufacturers, business organizations, and also government agencies which are included in current assets. This research aims to determine whether the inventory accounting treatment at the Bitung City Regional Revenue Agency is in accordance with PSAP No.5. The method used in this research is the descriptive qualitative method, a method that focuses on in-depth observation. From the results of this research, it can be shown that the inventory accounting treatment at the Bitung City Regional Revenue Agency is in accordance with Government Accounting Standards Statement No.05, seen from the classification, recognition, measurement, inventory costs and inventory disclosures, it is in accordance with PSAP No.05 Inventory Accounting